Understanding Health and Care Among Sex Workers Perspectives From Rhode Island - Macon, Claire; Tai, Eden.; Lane, Sidney (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This book examines sex worker health and the concept of care among sex workers in Rhode Island using mixed methods research conceived of and led by Ocean State Advocacy (O$A), a grassroots collective of sex workers in Rhode Island. Drawing upon survey data, in-depth interview research, as well as ethnographic and grounded theory principle, this text provides a nuanced look at why sex workers face disparate health outcomes, what defines the area of sex worker health, and practices of care that exist among sex workers in Rhode Island. Throughout this book, the authors examine how criminalization and stigma impact care and why sex workers find themselves in a distinctly challenging position when trying to stay healthy and well. Throughout this book, the authors explore both these vulnerabilities and sources of strength among the sex work community with the goal of gaining a better understanding of what sex workers in Rhode Island need for a healthier future. This book will be of interest to scholars and students within the fields of Sociology, Gender and Sexuality Studies, Labor Studies, Public Health, Social Medicine, Medical Humanities, and Medical Education. Eden Tai is a queer mixed Taiwanese artist and researcher whose work aims to make people feel closer to home in their bodies, in relationship to others, and in the places they live. Her interest in oral histories and community archives guides her research as a member of O$A, as well as her personal arts practice.
1: Introduction: Defining Sex Worker Health in Rhode Island -- 2: Sex Worker Conceptions of Health and Meeting Personal Health Needs -- 3: Community Care: How Sex Workers Care for Each Other -- 4: Primary Care and the Role of Coordinated Care in Meeting the Needs of Sex Workers -- 5: Emergency Care and Specialist Care: Care that Comes and Goes -- 6: Best Practices for Care Providers in Supporting Sex Workers and Conclusion.
Keywords: Health; Sex; Medical care; Medical anthropology; Gender and Health; Sexuality Studies; Gender Studies; Health Care; Medical Anthropology